Analisa Perbandingan Pengasutan Motor Induksi 3 Fasa Soft Starter IGBT Berbasis Sine-Triangle dan Sine-Sawtooth PWM Menggunakan Matlab Simulink - Anwar, Miftakhul Umam Ulil; Nugroho, Dedi; Nugroho, Agus Adhi (Elektrika, 2022)
TThe induction motor is the electric drive for industry so special attention is needed for maintainance and control system. Induction motors pulling high starting currents at starting. Various starting methods have been developed to overcome this problem, one of which is the Direct On-Line starting method. This method is the most common method because it is the easiest and cheapest to use, but there is high inrush current arround 6-8 times the nominal current will pulled by induction motor when using this method. This starting current can cause several disturbances, both from the electricity network, damaging the motor and can cause fatal losses to the electric power system.This research discusses the application of the Soft Starter starting method to a 3-phase induction motor to reduce the high starting current pulled by a 3-phase induction motor. The induction motor used in this study is a squirrel cage rotor type with 4kVA power, a rotational speed of 1430 r.p.m, a frequency of 50 Hz, and a voltage of 380 V. The Soft Starter system in this study uses 6 Insulated Gate Bipolar Transistor (IGBT)power electronics switches which are controlled using a sine-triangle PWM and sine - Sawtooth PWM. MATLAB SIMULINK is used to simulate the application of the soft starter starting method on a 3-phase induction motor.The results prove that the Soft Starter method is successful in reducing staring currents when compared to the Direct On-Line method. When using the Direct On-Line method the starting current is 77.29 78.80 A, when using the sine-triangle soft starter method the starting current is 60,46 61,46 A, and when using the sine-sawtooth soft starter method. starting 59,96 60,60 A. However, at steady state conditions, the Direct On-Line rotational speed is better than the Soft Starter because when using the Soft Starter method the voltage is cut. Soft St